E-book annotation adding method, electronic equipment and computer storage medium - WU FUJIANG; HUANG XINXIA (2019)
The invention discloses an electronic book annotation adding method, electronic equipment and a computer storage medium. The method comprises the following steps: when an electronic book is in a booklistening scene, determining to-be-annotated characters selected by a user according to a non-touch screen operation of the user; Stopping playing the content of the electronic book, and receiving voice annotation content input by a user; And in response to the voice annotation input completion instruction, stopping receiving the voice annotation content, and recovering playing of the electronic book content. According to the scheme, annotations can be added to the electronic book without manual operation of a user in the book listening scene, the problem that the annotation adding operation of the user in the book listening scene is complex is solved, the flexibility and convenience of adding the annotations to the electronic book are improved, and then the reading continuity and readingefficiency of the user are